Changes in the value orientations of adolescents in the period 1972–2018 - Radovanovic, Ivana D.; Spasić, Danijela; Radovanović, Dobrivoje (Sociološki pregled, 2022)
The current acceptance of value orientations by adolescents, changes in acceptance over time, and the connection with changes in social relations are undoubtedly of special interest to researchers, as well as certain segments of society. In this article, the results of the acceptance of the same value orientations at seven points in time, published in the works of different authors starting from 1972 as the first year in which data were available, were compared with the results of their acceptance at the eighth point, i.e., in 2018. The 2018 results were obtained by the author of this article, on a random sample of 832 secondary school students in Belgrade, with the same value orientations as in the previous seven papers: utilitarianism, hedonism, altruism, and activism. The number and type of value orientations are limited by the need to have the same ones throughout the time interval so that comparison is possible. The aim of the paper was: a) to determine the degree of desirability of these value orientations at the time of the research, and b) to determine the desirability changes and possible connection with social changes in the period from 1972 to 2018 (period of 46 years) by comparing the desirability of these value orientations in the same period. The data in previous surveys, before 2018, allowed comparison only in the mean values and calculation of the significance of the differences in them. The results obtained in that way showed the relative stability over time of the hedonic value orientation, a significant increase in the utilitarian value orientation and a significant decrease in the activist and altruistic value orientations. A logical analysis of these changes established their correspondence to the nature and the direction of changes in social relations in that period.